Method for preparing methane by catalyzing hydropyrolysis of waste polyolefin plastic through FCC waste rubber residue loaded metal Ru
By loading metal Ru catalyst on FCC waste rubber slag and performing hydropyrolysis treatment, the waste polyolefin plastics are successfully converted into highly selective methane at a lower temperature, solving the problems of waste rubber slag treatment and resource utilization, realizing the Efficient and low-cost plastic upgrade and recycling.
Patent Information
- Application Number
- CN202411383542.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art is difficult to efficiently convert waste polyolefin plastics into single product methane at lower temperatures, and the treatment of FCC waste slags has problems of environmental pollution and resource waste.
The cheap and easy-to-get FCC waste slag is used as a support and the metal Ru catalyst is supported, and the hydropyrolysis is carried out at 220-300°C. The catalyst activity is improved through calcination and ion exchange treatment, thereby achieving efficient preparation of methane.
The efficient conversion of waste polyolefin plastics into methane at lower temperatures, and the selectivity of gas products reaches more than 99%, solving the problems of resource waste and environmental pollution, and reducing energy consumption and costs.
Smart Images

Figure BDA0005070484730000101 
Figure BDA0005070484730000111 
Figure BDA0005070484730000112
Abstract
Description
Technical Field
[0001] The invention relates to the field of waste plastics upgrading and recycling, and in particular to a method for preparing methane by hydrogenating and pyrolyzing waste polyolefin plastics catalyzed by FCC waste rubber residue loaded with metal Ru. Background Art
[0002] The unreasonable disposal of waste plastics has caused serious environmental problems and waste of resources, and it is urgent to find effective methods to upgrade and recycle waste plastics. Chemical recycling methods can convert waste polyolefin plastics into high value-added chemicals with high selectivity. The most common methods are direct pyrolysis, catalytic pyrolysis, and hydrogenation pyrolysis. At present, the products of most chemical recycling technologies for waste polyolefin plastics are often mixtures with complex components and a wide distribution of carbon numbers, such as mixed liquids, paraffin, tar and other products. The reuse of downstream products of these products requires complex process separation, and the high cost of separation processes makes it difficult for existing methods to develop further. Therefore, developing a method with good catalytic activity that can efficiently convert waste polyolefin plastics into a single product is of great value to the transformation of polyolefin plastics into high-value products.
[0003] The production process of FCC catalyst will produce wastewater containing a large amount of suspended solids. The suspended solids in the wastewater need to be settled, filtered and cut, thereby producing a large amount of FCC catalyst waste rubber residue (FCC waste rubber residue for short). my country discharges about 80,000 tons of FCC waste rubber residue every year. At present, it is mainly treated by landfilling. This treatment method leads to serious environmental pollution, economic burden and waste of resources. FCC waste rubber residue contains a large amount of amorphous SiO2-Al2O3 and some Y molecular sieves and ZSM-5 molecular sieves, which are commonly used catalysts for catalytic pyrolysis of polyolefin plastics. FCC waste rubber residue contains a large amount of rare earths that can promote the generation of carbon cation intermediates and improve the catalytic activity of hydrogenation pyrolysis of polyolefin plastics. Loading metal Ru on FCC waste rubber residue as a catalyst for hydrogenation pyrolysis of waste polyolefin plastics can not only achieve the upgrading and recycling of waste polyolefin plastics, but also broaden the road for the resource reuse of FCC waste rubber residue.
[0004] Patent 202410550410.7 discloses a method and application of waste plastic hydrogenation catalytic cracking and oil refining. This method uses ZSM-5 as a carrier and loads transition metals for plastic hydrogenation pyrolysis to produce pyrolysis oil. However, this method still has problems such as complex product composition, low selectivity of target products, and high reaction temperature. Zhang et al. (JACS, 2023, 145, 22836-22844) used Ru-based catalysts to design a two-step series method of pyrolysis (at 520°C)-hydrogenation pyrolysis (at 300°C) to convert mixed plastics into methane, with a methane selectivity of more than 99%. However, their method has problems such as complex operation, high reaction temperature, and low yield of gas products.
[0005] How to use FCC waste rubber residue, that is, the waste residue generated in the FCC preparation process as a raw material to prepare a catalyst, adopt a hydrogenation pyrolysis method, and prepare methane at a relatively low reaction temperature, has not been reported in the prior art. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention aims to provide a method for preparing methane by catalyzing the hydrogenation pyrolysis of waste polyolefin plastics by loading metal Ru on FCC waste rubber residue. The present invention uses cheap and easily available FCC waste rubber residue containing rare earth as a carrier, loading metal Ru, and can efficiently catalyze the hydrogenation pyrolysis of waste polyolefin plastics to prepare methane at a relatively low temperature. The yield of the gas product is close to 100%, and the product is single, almost only methane, and the selectivity of methane is more than 99%, which provides a solution for the upgrading and recycling of waste polyolefin plastics.
[0007] The technical solution adopted by the present invention to solve its technical problem is:
[0008] Put the RuCl3·3H2O calculated according to the required loading amount into a beaker, add an appropriate amount of deionized water and stir until the solid is completely dissolved. Grind the treated FCC waste slag into powder and pour it into the RuCl3·3H2O aqueous solution, stir evenly and dry it naturally at room temperature, then put it into a muffle furnace and calcine it at a certain temperature for a certain time to obtain an x%Ru / slag catalyst; where "x%" represents the loading amount of metal Ru, and x% is 0.5-7wt.%.
[0009] Mix x%Ru / slag catalyst and waste polyolefin plastics evenly and put them into a stainless steel high-pressure reactor. Put in a magnetic stirrer and seal the reactor. Then, replace the air in the reactor with hydrogen. After replacing it 5 times, fill it with 1-5MPa hydrogen, turn on the magnetic stirring, and react at 220-300℃ for 1-12h. After the reaction, place the reactor in a water bath, wait for the temperature of the reactor to drop to room temperature, and collect the pyrolysis gas with a gas collection bag. The gas phase product is further analyzed by gas chromatography, where the yield of the gas product is close to 100%, and the selectivity of methane in the gas product reaches more than 99%.
[0010] Furthermore, the treated FCC waste rubber residue is immersed in an aqueous solution of RuCl3·3H2O and the calcination temperature is 300-500°C, and the calcination time is 2-6 hours.
[0011] Furthermore, the mass ratio of the x%Ru / slag catalyst to the waste polyolefin plastic is 0.02 to 0.2.
[0012] Preferably, the mass ratio of the x%Ru / slag catalyst to the waste polyolefin plastic is 0.05 to 0.1.
[0013] Preferably, the reaction temperature is 240-270°C.
[0014] Preferably, the initial hydrogen pressure is 4-5 MPa.
[0015] Preferably, the reaction time is 2 to 6 hours.
[0016] The treated FCC waste rubber residue is processed by calcining and ion exchange in sequence, specifically: putting the dried powdered FCC waste rubber residue in a muffle furnace and calcining it at 450-650°C for 3-7h, then pouring the calcined FCC waste rubber residue into an ammonium chloride solution with a concentration of 0.5-2mol / L, the ratio of the FCC waste rubber residue to the ammonium chloride solution is 1g / (5-25)mL, stirring and impregnating it at a temperature of 70-95°C for 1-3h for ion exchange; washing the impregnated FCC waste rubber residue with deionized water for 3-5 times, drying it after washing, and then calcining it at 400-650°C for 1-5h in a muffle furnace, repeating the process of impregnation, washing, drying and calcining for 3-5 times to achieve a high ion exchange degree, and obtaining the FCC waste rubber residue after ion exchange.
[0017] Wherein, the total mass of FCC waste rubber residue is 100%, the mass content of Al in the dry FCC waste rubber residue is 10% to 30% in terms of Al2O3, the mass content of Si is 30% to 70% in terms of SiO2, the mass content of La is 1% to 15% in terms of La2O3, the mass content of Ce is 3% to 20% in terms of CeO2, and the mass content of Fe is 0.1% to 2% in terms of Fe2O3. Other impurities account for a small proportion and can be ignored.
[0018] Beneficial Effects of the Invention
[0019] (1) The catalyst of the present invention has a simple preparation process and good catalytic activity, and can efficiently convert waste polyolefin plastics into a single methane product, with a methane selectivity of more than 99%.
[0020] (2) The present invention can efficiently convert polyolefin plastics at 240°C, which greatly reduces the reaction temperature and saves energy compared to other technologies.
[0021] (3) Using FCC waste rubber residue as a carrier saves costs and provides an effective way to efficiently utilize FCC waste rubber residue solid waste. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the gas chromatogram of the gas product of Example 8. DETAILED DESCRIPTION
[0023] The present invention will be further described with reference to the following examples, but it should be understood that these examples are only for illustration and should not be construed as limitations of the present invention.
[0024] The FCC waste rubber residue used in the specific embodiment of the present invention is sourced from the Qilu Branch of China Petrochemical Corporation. The composition analysis of the FCC waste rubber residue is as follows:
[0025] The FCC waste rubber residue was placed in an oven and dried at 120°C for 48 hours to remove excess moisture. The main components in the FCC waste rubber residue were analyzed by X-ray fluorescence spectrometry. Calculated by oxide mass fraction, it was measured that SiO2 accounted for 51.1%, Al2O3 accounted for 18.9%, CeO2 accounted for 9.6%, La2O3 accounted for 6.5%, Na2O accounted for 5.8%, GaO accounted for 2.6%, MgO accounted for 0.8%, Fe2O3 accounted for 0.4%, and other impurities accounted for a small proportion and could be ignored.
[0026] The dried powdered FCC waste rubber residue was placed in a muffle furnace and roasted at 550℃ for 5h. 50g of the roasted FCC waste rubber residue was poured into 500ml of 1mol / L ammonium chloride solution and stirred and immersed at 90℃ for 1.5h. The impregnated FCC waste rubber residue was washed with deionized water for 3 to 5 times, and then dried. The dried FCC waste rubber residue was placed in a muffle furnace and roasted at 550℃ for 3h. The process of impregnation, washing, drying and roasting was repeated 5 times to obtain the FCC waste rubber residue after ion exchange.
[0027] Example 1
[0028] 0.362g of RuCl3·3H2O was placed in a beaker, and an appropriate amount of deionized water was added and stirred until the solid was completely dissolved. 2g of FCC waste rubber residue after ion exchange was ground into powder and poured into the RuCl3·3H2O aqueous solution, stirred evenly and dried naturally at room temperature, and then placed in a muffle furnace and calcined at 400℃ for 5h to obtain a 7% Ru / rubber residue catalyst.
[0029] 0.1g 7%Ru / slag catalyst and 1.0g LDPE were mixed evenly and loaded into a stainless steel autoclave, and a magnetic stirrer was placed in the autoclave and the autoclave was sealed. Subsequently, the air in the autoclave was replaced with hydrogen, and 4MPa of hydrogen was filled in after five replacements, and magnetic stirring was turned on, and the reaction was carried out at 240°C for 2h; after the reaction was completed, the autoclave was placed in a water bath, and the temperature of the autoclave was lowered to room temperature, and the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0030] Example 2
[0031] 0.155g of RuCl3·3H2O was placed in a beaker, and an appropriate amount of deionized water was added and stirred until the solid was completely dissolved. 2g of FCC waste rubber residue after ion exchange was ground into powder and poured into the RuCl3·3H2O aqueous solution, stirred evenly and dried naturally at room temperature, and then placed in a muffle furnace and calcined at 400℃ for 5h to obtain a 3% Ru / rubber residue catalyst.
[0032] 0.1g 3%Ru / slag catalyst and 1.0g LDPE were mixed and loaded into a stainless steel autoclave, and a magnetic stirrer was placed in the autoclave and sealed. Subsequently, the air in the autoclave was replaced with hydrogen, and 4MPa of hydrogen was filled in after five replacements. The magnetic stirrer was turned on and the reaction was carried out at 240°C for 2h. After the reaction was completed, the autoclave was placed in a water bath, and the temperature of the autoclave was lowered to room temperature. The pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0033] Example 3
[0034] 0.026g of RuCl3·3H2O was placed in a beaker, and an appropriate amount of deionized water was added and stirred until the solid was completely dissolved. 2g of FCC waste rubber residue after ion exchange was ground into powder and poured into the RuCl3·3H2O aqueous solution, stirred evenly and dried naturally at room temperature, and then placed in a muffle furnace and calcined at 400℃ for 5h to obtain a 0.5% Ru / rubber residue catalyst.
[0035] 0.1g 0.5% Ru / slag catalyst and 1.0g LDPE were mixed evenly and loaded into a stainless steel autoclave, and a magnetic stirrer was placed in the autoclave and the autoclave was sealed. Subsequently, the air in the autoclave was replaced with hydrogen, and after five replacements, 4MPa of hydrogen was filled in, and magnetic stirring was turned on, and the reaction was carried out at 240°C for 2h; after the reaction was completed, the autoclave was placed in a water bath, and when the temperature of the autoclave dropped to room temperature, the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0036] Example 4
[0037] 0.155g of RuCl3·3H2O was placed in a beaker, and an appropriate amount of deionized water was added and stirred until the solid was completely dissolved. 2g of FCC waste rubber residue after ion exchange was ground into powder and poured into the RuCl3·3H2O aqueous solution, stirred evenly and dried naturally at room temperature, and then placed in a muffle furnace and calcined at 400℃ for 3h to obtain a 3% Ru / rubber residue catalyst.
[0038] 0.1g 3%Ru / slag catalyst and 1.0g LDPE were mixed evenly and loaded into a stainless steel autoclave, and a magnetic stirrer was placed in the autoclave and the autoclave was sealed. Subsequently, the air in the autoclave was replaced with hydrogen, and after five replacements, 4MPa of hydrogen was filled in, and magnetic stirring was turned on, and the reaction was carried out at 220°C for 2h; after the reaction was completed, the autoclave was placed in a water bath, and when the temperature of the autoclave dropped to room temperature, the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0039] Example 5
[0040] 0.155g of RuCl3·3H2O was placed in a beaker, and an appropriate amount of deionized water was added and stirred until the solid was completely dissolved. 2g of FCC waste rubber residue after ion exchange was ground into powder and poured into the RuCl3·3H2O aqueous solution, stirred evenly and dried naturally at room temperature, and then placed in a muffle furnace and calcined at 400℃ for 3h to obtain a 3% Ru / rubber residue catalyst.
[0041] 0.1g 3%Ru / slag catalyst and 1.0g LDPE were mixed evenly and loaded into a stainless steel high-pressure reactor, and a magnetic stirrer was placed and the reactor was sealed. Subsequently, the air in the reactor was replaced with hydrogen, and 4MPa of hydrogen was filled in after five replacements, and magnetic stirring was turned on, and the reaction was carried out at 300°C for 2h; after the reaction was completed, the reactor was placed in a water bath, and the temperature of the reactor was lowered to room temperature, and the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0042] Example 6
[0043] 0.155g of RuCl3·3H2O was placed in a beaker, and an appropriate amount of deionized water was added and stirred until the solid was completely dissolved. 2g of FCC waste rubber residue after ion exchange was ground into powder and poured into the RuCl3·3H2O aqueous solution, stirred evenly and dried naturally at room temperature, and then placed in a muffle furnace and calcined at 400℃ for 3h to obtain a 3% Ru / rubber residue catalyst.
[0044] 0.1g 3%Ru / slag catalyst and 1.0g LDPE were mixed evenly and loaded into a stainless steel autoclave, and a magnetic stirrer was placed in the autoclave and the autoclave was sealed. Subsequently, the air in the autoclave was replaced with hydrogen, and after five replacements, 4MPa of hydrogen was filled in, and magnetic stirring was turned on, and the reaction was carried out at 250°C for 2h; after the reaction was completed, the autoclave was placed in a water bath, and when the temperature of the autoclave dropped to room temperature, the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0045] Example 7
[0046] 0.155g of RuCl3·3H2O was placed in a beaker, and an appropriate amount of deionized water was added and stirred until the solid was completely dissolved. 2g of FCC waste rubber residue after ion exchange was ground into powder and poured into the RuCl3·3H2O aqueous solution, stirred evenly and dried naturally at room temperature, and then placed in a muffle furnace and calcined at 400℃ for 5h to obtain a 3% Ru / rubber residue catalyst.
[0047] 0.1g 3%Ru / slag catalyst and 1.0g LDPE were mixed evenly and loaded into a stainless steel high-pressure reactor, and a magnetic stirrer was placed and the reactor was sealed. Subsequently, the air in the reactor was replaced with hydrogen, and 4MPa of hydrogen was filled after five replacements, and magnetic stirring was turned on, and the reaction was carried out at 250°C for 12h; after the reaction was completed, the reactor was placed in a water bath, and the temperature of the reactor was lowered to room temperature, and the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0048] Example 8
[0049] 0.155g of RuCl3·3H2O was placed in a beaker, and appropriate amount of deionized water was added and stirred until the solid was completely dissolved. 2g of FCC waste rubber residue after ion exchange was ground into powder and poured into the RuCl3·3H2O aqueous solution, stirred evenly and dried naturally at room temperature, and then placed in a muffle furnace and calcined at 400℃ for 5h to obtain a 3% Ru / rubber residue catalyst.
[0050] 0.1g 3%Ru / slag catalyst and 1.0g LDPE were mixed evenly and loaded into a stainless steel autoclave, and a magnetic stirrer was placed in the autoclave and the autoclave was sealed. Subsequently, the air in the autoclave was replaced with hydrogen, and after five replacements, 4MPa of hydrogen was filled in, and magnetic stirring was turned on, and the reaction was carried out at 250°C for 6h; after the reaction was completed, the autoclave was placed in a water bath, and when the temperature of the autoclave dropped to room temperature, the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0051] Example 9
[0052] 0.155g of RuCl3·3H2O was placed in a beaker, and an appropriate amount of deionized water was added and stirred until the solid was completely dissolved. 2g of FCC waste rubber residue after ion exchange was ground into powder and poured into the RuCl3·3H2O aqueous solution, stirred evenly and dried naturally at room temperature, and then placed in a muffle furnace and calcined at 400℃ for 5h to obtain a 3% Ru / rubber residue catalyst.
[0053] 0.02g of 3%Ru / slag catalyst and 1.0g of LDPE were mixed evenly and loaded into a stainless steel autoclave, and a magnetic stirrer was placed in the autoclave and the autoclave was sealed. Subsequently, the air in the autoclave was replaced with hydrogen, and after five replacements, 4MPa of hydrogen was filled in, and magnetic stirring was turned on, and the reaction was carried out at 250°C for 6h; after the reaction was completed, the autoclave was placed in a water bath, and when the temperature of the autoclave dropped to room temperature, the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0054] Example 10
[0055] 0.155g of RuCl3·3H2O was placed in a beaker, and an appropriate amount of deionized water was added and stirred until the solid was completely dissolved. 2g of FCC waste rubber residue after ion exchange was ground into powder and poured into the RuCl3·3H2O aqueous solution, stirred evenly and dried naturally at room temperature, and then placed in a muffle furnace and calcined at 400℃ for 5h to obtain a 3% Ru / rubber residue catalyst.
[0056] 0.2g of 3%Ru / slag catalyst and 1.0g of LDPEP were mixed evenly and loaded into a stainless steel high-pressure reactor, and a magnetic stirrer was placed in the reactor and sealed. Subsequently, the air in the reactor was replaced with hydrogen, and 4MPa of hydrogen was filled in after five replacements, and magnetic stirring was turned on, and the reaction was carried out at 250°C for 6h; after the reaction was completed, the reactor was placed in a water bath, and when the temperature of the reactor dropped to room temperature, the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0057] Embodiment 11
[0058] 0.155g of RuCl3·3H2O was placed in a beaker, and an appropriate amount of deionized water was added and stirred until the solid was completely dissolved. 2g of FCC waste rubber residue after ion exchange was ground into powder and poured into the RuCl3·3H2O aqueous solution, stirred evenly and dried naturally at room temperature, and then placed in a muffle furnace and calcined at 400℃ for 5h to obtain a 3% Ru / rubber residue catalyst.
[0059] 0.1g 3%Ru / slag catalyst and 1.0g LDPE were mixed evenly and loaded into a stainless steel autoclave, and a magnetic stirrer was placed in the autoclave and the autoclave was sealed. Subsequently, the air in the autoclave was replaced with hydrogen, and after five replacements, 2MPa of hydrogen was filled in, and magnetic stirring was turned on, and the reaction was carried out at 250°C for 6h; after the reaction was completed, the autoclave was placed in a water bath, and when the temperature of the autoclave dropped to room temperature, the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0060] Example 12
[0061] 0.155g of RuCl3·3H2O was placed in a beaker, and an appropriate amount of deionized water was added and stirred until the solid was completely dissolved. 2g of FCC waste rubber residue after ion exchange was ground into powder and poured into the RuCl3·3H2O aqueous solution, stirred evenly and dried naturally at room temperature, and then placed in a muffle furnace and calcined at 400℃ for 5h to obtain a 3% Ru / rubber residue catalyst.
[0062] 0.1g 3%Ru / slag catalyst and 1.0g LDPE were mixed evenly and loaded into a stainless steel autoclave, and a magnetic stirrer was placed in the autoclave and the autoclave was sealed. Subsequently, the air in the autoclave was replaced with hydrogen, and after five replacements, 5MPa of hydrogen was filled in, and magnetic stirring was turned on, and the reaction was carried out at 250°C for 6h; after the reaction was completed, the autoclave was placed in a water bath, and when the temperature of the autoclave dropped to room temperature, the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0063] Embodiment 13
[0064] 0.155g of RuCl3·3H2O was placed in a beaker, and an appropriate amount of deionized water was added and stirred until the solid was completely dissolved. 2g of FCC waste rubber residue after ion exchange was ground into powder and poured into the RuCl3·3H2O aqueous solution, stirred evenly and dried naturally at room temperature, and then placed in a muffle furnace and calcined at 400℃ for 5h to obtain a 3% Ru / rubber residue catalyst.
[0065] 0.1g 3%Ru / slag catalyst and 1.0g HDPE were mixed evenly and loaded into a stainless steel autoclave, and a magnetic stirrer was placed in the autoclave and the autoclave was sealed. Subsequently, the air in the autoclave was replaced with hydrogen, and after five replacements, 4MPa of hydrogen was filled in, and magnetic stirring was turned on, and the reaction was carried out at 250°C for 6h; after the reaction was completed, the autoclave was placed in a water bath, and when the temperature of the autoclave dropped to room temperature, the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0066] Embodiment 14
[0067] 0.155g of RuCl3·3H2O was placed in a beaker, and an appropriate amount of deionized water was added and stirred until the solid was completely dissolved. 2g of FCC waste rubber residue after ion exchange was ground into powder and poured into the RuCl3·3H2O aqueous solution, stirred evenly and dried naturally at room temperature, and then placed in a muffle furnace and calcined at 400℃ for 5h to obtain a 3% Ru / rubber residue catalyst.
[0068] 0.1g 3%Ru / slag catalyst and 1.0g PP were mixed evenly and loaded into a stainless steel high-pressure reactor, and a magnetic stirrer was placed in the reactor and sealed. Subsequently, the air in the reactor was replaced with hydrogen, and 4MPa of hydrogen was filled in after five replacements, and magnetic stirring was turned on, and the reaction was carried out at 250°C for 6h; after the reaction was completed, the reactor was placed in a water bath, and the temperature of the reactor was lowered to room temperature, and the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0069] Embodiment 15
[0070] 0.155g of RuCl3·3H2O was placed in a beaker, and an appropriate amount of deionized water was added and stirred until the solid was completely dissolved. 2g of FCC waste rubber residue after ion exchange was ground into powder and poured into the RuCl3·3H2O aqueous solution, stirred evenly and dried naturally at room temperature, and then placed in a muffle furnace and calcined at 400℃ for 5h to obtain a 3% Ru / rubber residue catalyst.
[0071] 0.1g 3%Ru / slag catalyst, 0.25g LDPE, 0.25g HDPE, 0.25g PP, 0.25g PS were mixed evenly and loaded into a stainless steel high-pressure reactor, and a magnetic stirrer was placed and the reactor was sealed. Subsequently, the air in the reactor was replaced with hydrogen, and after five replacements, 5MPa of hydrogen was filled in, and magnetic stirring was turned on, and the reaction was carried out at 300°C for 6h; after the reaction was completed, the reactor was placed in a water bath, and the temperature of the reactor was lowered to room temperature, and the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0072] Comparative Example 1
[0073] 0.1g of FCC residue catalyst after ion exchange and 1.0g of LDPE were mixed and evenly loaded into a stainless steel high-pressure reactor, and a magnetic stirrer was placed and the reactor was sealed. Subsequently, the air in the reactor was replaced with hydrogen, and 4MPa of hydrogen was filled after five replacements, and magnetic stirring was turned on, and the reaction was carried out at 250°C for 6h; after the reaction was completed, the reactor was placed in a water bath, and the temperature of the reactor was lowered to room temperature, and the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0074] Comparative Example 2
[0075] 0.155g of RuCl3·3H2O was placed in a beaker, and an appropriate amount of deionized water was added and stirred until the solid was completely dissolved. 2g of HY molecular sieve (purchased from the catalyst factory of Nankai University) was ground into powder and poured into the RuCl3·3H2O aqueous solution. After stirring evenly, it was naturally dried at room temperature. After drying, it was placed in a muffle furnace and calcined at 400°C for 5h to obtain a 3% Ru / HY catalyst.
[0076] 0.1g 3% Ru / HY catalyst and 1.0g LDPE were mixed evenly and loaded into a stainless steel high-pressure reactor, and a magnetic stirrer was placed and the reactor was sealed. Subsequently, the air in the reactor was replaced with hydrogen, and 4MPa of hydrogen was filled in after five replacements, and magnetic stirring was turned on, and the reaction was carried out at 250°C for 6h; after the reaction was completed, the reactor was placed in a water bath, and the temperature of the reactor was lowered to room temperature, and the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0077] Comparative Example 3
[0078] 0.155g of RuCl3·3H2O was placed in a beaker, and an appropriate amount of deionized water was added and stirred until the solid was completely dissolved. 2g of Hβ molecular sieve (purchased from the catalyst factory of Nankai University) was ground into powder and poured into the RuCl3·3H2O aqueous solution. After stirring evenly, it was naturally dried at room temperature. After drying, it was placed in a muffle furnace and calcined at 400°C for 5h to obtain a 3% Ru / Hβ catalyst.
[0079] 0.1g 3%Ru / Hβ catalyst and 1.0g LDPE were mixed and loaded into a stainless steel high-pressure reactor, and a magnetic stirrer was placed in the reactor and sealed. Subsequently, the air in the reactor was replaced with hydrogen, and 4MPa of hydrogen was filled in after five replacements, and magnetic stirring was turned on, and the reaction was carried out at 250°C for 6h; after the reaction was completed, the reactor was placed in a water bath, and the temperature of the reactor was lowered to room temperature, and the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0080] Comparative Example 4
[0081] 0.494g Co(NO3)2·6H2O was placed in a beaker, and an appropriate amount of deionized water was added and stirred until the solid was completely dissolved. 2g of FCC waste rubber residue after ion exchange was ground into powder and poured into the aqueous solution of Co(NO3)2·6H2O, stirred evenly and dried naturally at room temperature, and then placed in a muffle furnace and calcined at 400℃ for 5h to obtain a 5% Co / slag catalyst.
[0082] 0.5g of 5% Co / slag catalyst and 1.5g of LDPE were mixed evenly and loaded into a stainless steel high-pressure reactor, and a magnetic stirrer was placed and the reactor was sealed. Subsequently, the air in the reactor was replaced with hydrogen, and 3MPa of hydrogen was filled in after five replacements, and magnetic stirring was turned on, and the reaction was carried out at 280°C for 24h; after the reaction was completed, the reactor was placed in a water bath, and the temperature of the reactor was lowered to room temperature, and the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0083] Comparative Example 5
[0084] 0.723g Fe(NO3)3·9H2O was placed in a beaker, and an appropriate amount of deionized water was added and stirred until the solid was completely dissolved. 2g of FCC waste slag after ion exchange was ground into powder and poured into the aqueous solution of Fe(NO3)3·9H2O, stirred evenly and dried naturally at room temperature, and then placed in a muffle furnace and calcined at 400℃ for 5h to obtain a 5% Fe / slag catalyst.
[0085] 0.5g of 5% Fe / slag catalyst and 1.5g of LDPE were mixed evenly and loaded into a stainless steel high-pressure reactor, and a magnetic stirrer was placed and the reactor was sealed. Subsequently, the air in the reactor was replaced with hydrogen, and 3MPa of hydrogen was filled in after five replacements, and magnetic stirring was turned on, and the reaction was carried out at 280°C for 24h; after the reaction was completed, the reactor was placed in a water bath, and the temperature of the reactor was lowered to room temperature, and the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0086] Comparative Example 6
[0087] Put 0.495g Ni(NO3)2·6H2O in a beaker, add appropriate amount of deionized water and stir until the solid is completely dissolved. Grind 2g of FCC waste rubber residue after ion exchange into powder and pour it into the aqueous solution of Ni(NO3)2·6H2O. Stir well and dry it naturally at room temperature. After drying, put it into a muffle furnace and calcine it at 400℃ for 5h to obtain a 5% Ni / rubber residue catalyst.
[0088] 0.5g of 5% Ni / slag catalyst and 1.5g of LDPE were mixed evenly and loaded into a stainless steel high-pressure reactor, and a magnetic stirrer was placed and the reactor was sealed. Subsequently, the air in the reactor was replaced with hydrogen, and 3MPa of hydrogen was filled after five replacements, and magnetic stirring was turned on, and the reaction was carried out at 280°C for 24h; after the reaction was completed, the reactor was placed in a water bath, and the temperature of the reactor was lowered to room temperature, and the pyrolysis gas was collected with a gas collection bag, and the gas phase product was further analyzed by gas chromatography.
[0089] Table 1 Product yields of the reactions in Examples 1 to 11 and Comparative Examples
[0090]
[0091]
[0092] Table 2 Compositions of gas products in Examples 1 to 11 and Comparative Examples
[0093]
[0094]
[0095] The product yields of the above examples and control examples are shown in Table 1; the gas phase composition is shown in Table 2. In Example 3, due to the low Ru loading and short reaction time, the gas product yield is low, and the gas product yield and methane selectivity can be improved by extending the reaction time. In Example 4, the reaction time of LDPE at a relatively low temperature is too short, so the gas product yield is low.
[0096] Ru / slag has excellent catalytic activity. Under appropriate conditions, there is basically no residual solid, the raw material is completely converted into gas products, and the composition of the gas products is mainly methane. Example 8 completely converts LDPE into gas products at a relatively low temperature (250°C), and the methane selectivity reaches the highest 99.1%. From the comparison between Example 8 and Control Example 1, it can be seen that without the addition of Ru / slag catalyst, there is almost no cracking reaction of LDPE, indicating that the Ru / slag catalyst plays a key role in the reaction. From the comparison between Example 8 and Control Examples 2-3, it can be seen that the selectivity of 3%Ru / slag for methane is much higher than that of 3%Ru / HY and 3%Ru / Hβ, indicating that the slag carrier plays a key role in improving the selectivity of methane. From the comparison between Example 11 and Control Examples 4-6, it can be seen that although the reaction conditions of Ru / slag catalyst are milder than those of Control Examples 4-6, it still shows better catalytic activity and methane selectivity than Co, Fe, and Ni / slag catalysts.
[0097] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing methane by hydrogenation pyrolysis of waste polyolefin plastics catalyzed by metal Ru loaded on FCC waste rubber residue, characterized in that: The method steps are as follows: (1) A catalyst is prepared by loading metal Ru on FCC waste slag after calcination and ion exchange treatment, which is recorded as "x% Ru / slag", where "x%" represents the loading amount of metal Ru, and x% is 0.5-7wt.%; (2) x%Ru / slag catalyst and waste polyolefin plastic are mixed in proportion, loaded into a reactor, and magnetic stirring is turned on to carry out hydrogenation pyrolysis reaction in a hydrogen atmosphere. After the reaction is completed, the gas and solid-liquid mixed products are collected separately, and the main component of the product is methane.
2. The method for preparing methane by catalyzing the hydrogenation and pyrolysis of waste polyolefin plastics by using metal Ru loaded on FCC waste rubber residue according to claim 1, characterized in that: The preparation method of the x%Ru / slag catalyst is as follows: FCC waste slag is calcined at 450-650°C for 3-7h, and after calcination, poured into an ammonium chloride solution for ion exchange; Wash, dry, and then calcine at 400-650°C for 1-5h, repeat the process of impregnation, washing, drying and calcination 2-6 times to obtain the treated FCC waste rubber residue; put RuCl3·3H2O calculated according to the required loading amount into a beaker, add deionized water and stir until the solid is completely dissolved; grind the treated FCC waste rubber residue into powder and pour it into the RuCl3·3H2O aqueous solution, stir evenly and dry naturally at room temperature, and then put it into a muffle furnace for calcination to obtain a x%Ru / slag catalyst.
3. The method for preparing methane by hydrogenation pyrolysis of waste polyolefin plastics catalyzed by metal Ru loaded on FCC waste rubber residue according to claim 2, characterized in that: The calcination temperature is 300-500°C, and the calcination time is 2-6 hours.
4. The method for preparing methane by hydrogenation pyrolysis of waste polyolefin plastics catalyzed by metal Ru loaded on FCC waste rubber residue according to claim 2, characterized in that: The ratio of the FCC waste rubber residue to the ammonium chloride solution is 1 g / (5-25) mL; the immersion temperature is 70-95° C., and the immersion time is 1-3 hours.
5. The method for preparing methane by hydrogenation pyrolysis of waste polyolefin plastics catalyzed by metal Ru loaded on FCC waste rubber residue according to claim 1, characterized in that: The mass ratio of x%Ru / slag catalyst to waste polyolefin plastic is 0.02-0.
2.
6. The method for preparing methane by hydrogenation pyrolysis of waste polyolefin plastics catalyzed by metal Ru loaded on FCC waste rubber residue according to claim 1, characterized in that: The reaction temperature of the hydrogenation pyrolysis reaction is 220-300° C., the initial hydrogen pressure is 1-6 MPa, and the reaction time is 1-12 hours.
7. The method for preparing methane by hydrogenation pyrolysis of waste polyolefin plastics catalyzed by metal Ru loaded on FCC waste rubber residue according to claim 6, characterized in that: The reaction temperature of the hydrogenation pyrolysis is 240-270° C., the initial hydrogen pressure is 4-5 MPa, and the reaction time is 2-6 hours.
Citation Information
Patent Citations
Waste plastic hydrogenation catalytic cracking oil refining method and application
CN118460234A
Cited By
Method for preparing methane by catalyzing polyolefin plastic hydrocracking through ruthenium-based cerium dioxide
CN121449485A